Trace level detection of Pb2+ ion using organic ligand as fluorescent-on probes in aqueous media - Maria Sadia; Jehangir Khan; Rizwan Khan; Syed Wadood Ali Shah; Adil Zada; Muhammad Zahoor; Riaz Ullah; Essam A. Ali (Heliyon)
In this study, an optical sensor, JA/(2,6-di((E)-benzylidene)cyclohexan-1-one), was synthesized and characterized using 1H NMR and FT-IR spectroscopy. The sensor exhibited high efficiency and selectivity in detecting Pb2+ ions, even in the presence of potential interfering ions such as Mn2+, Cu2+, Co2+, Cr3+, Ni2+, Ce3+, Hg2+, and Cd2+ in aqueous solutions. The interaction of JA with Pb2+ resulted in a significant enhancement of fluorescence intensity, suggesting the formation of a stable complex. A 2:1 binding ratio between JA and Pb2+ was confirmed through fluorometric analysis, absorption spectra, and theoretical calculations (DFT). The association constant for the complex was calculated to be 3 × 106 M−2. The sensor demonstrated high sensitivity towards Pb2+ with a detection limit of 5 × 10−7 M. Additionally, JA was successfully reused by applying EDTA to release Pb2+ from the sensor. Real sample analysis under optimized conditions of pH, time, and concentration of JA and Pb2+ further validated the practical applicability of the sensor.